The influence of simvastatin in induced peritoneal fibrosis in rats by peritoneal dialysis solution with glucosis 4.25% - Baroni,Gilberto (2012)
PURPOSE: To investigate the influence of using simvastatin on the peritoneal fibrosis induced in rats using peritoneal dialysis solution with glucoses 4.25%. METHODS: Prospective controlled study in 20 non-uremic Wistar rats. The animals received a peritoneal infusion of 10 ml/100 g of peritoneal dialysis solution glucose 4.25% on a daily basis. The animals were divided in two groups: experimental and control. The experimental group received simvastatin 4 mg/kg/d, by a gastric tube. The control group did not receive any drug. The follow-up was 21 and 49 days. At the end, one surgical procedure was performed to get histological samples of visceral and parietal peritoneum. The samples were analyzed using Hematoxylin Eosin and Sirius Red, to evaluate the severity of the fibrosis. RESULTS: The analysis showed that the intensity of the fibrosis, the peritoneal thickness and the cell number in experimental and control groups were not statistically significant different in experimental and control groups. CONCLUSION: The simvastatin do not decrease the intensity of fibrosis on the peritoneal membrane that happens on rats on peritoneal dialysis.